Solving difference equations by forward difference operator method (2010)
In this paper a forward difference operator method was used to solve a set of difference equations. We also find the particular solution of the nonhomogeneous difference equations with constant coefficients. In this case, a new operator call the forward difference operator Δr,s, defined as Δr,s yn = r yn+1 - s yn, was introduced. Some of the properties of this new operator were also investigated.